1990
DOI: 10.1021/jm00170a023
|View full text |Cite
|
Sign up to set email alerts
|

Brain targeting of anti-HIV nucleosides: synthesis and in vitro and in vivo studies of dihydropyridine derivatives of 3'-azido-2',3'-dideoxyuridine and 3'-azido-3'-deoxythymidine

Abstract: A significant number of patients with AIDS and AIDS-related complex develop neurological complications. Therefore, it is critical that anti-HIV agents penetrate the blood-brain barrier and suppress viral replication in the brain. In an effort to increase the brain delivery of anti-HIV nucleosides, in vitro and in vivo pharmacokinetics of dihydropyridine derivatives of 3'-azido-2',3'-dideoxyuridine (AzddU, AZDU, or CS-87) and 3'-azido-3'-deoxythymidine (AZT, Zidovudine) have been studied. In vitro studies of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(31 citation statements)
references
References 8 publications
2
29
0
Order By: Relevance
“…Steady-state prodrug concentrations were not significantly different in CSF and brain tissue, whereas the ddl concentrations in brain tissue were nearly twofold higher than those in CSF at steady-state because of an apparent slower rate of efflux of ddl from brain tissue. (mm) tIn- (mm) k., (min-') khyd (mm-) (g-min/ml) (>g. min/ml) (ml/mi/kg) system initially developed by Bodor et al (5), but the degrees of enhancement of delivery of AZT to CNS that have been reported are highly variable from laboratory to laboratory (7,10,20,21). Recent findings that a series of lipophilic 6-halo-ddPs exhibit activity against HIV in vitro (11,18,35,36) and that their activities were completely abrogated in the presence of an ADA inhibitor (23,35,36) coupled with preliminary indications of enhanced CNS delivery via this approach in rats (2), suggest a promising new enzyme-based strategy for improving the delivery of dideoxynucleosides to the CNS.…”
Section: Resultsmentioning
confidence: 99%
“…Steady-state prodrug concentrations were not significantly different in CSF and brain tissue, whereas the ddl concentrations in brain tissue were nearly twofold higher than those in CSF at steady-state because of an apparent slower rate of efflux of ddl from brain tissue. (mm) tIn- (mm) k., (min-') khyd (mm-) (g-min/ml) (>g. min/ml) (ml/mi/kg) system initially developed by Bodor et al (5), but the degrees of enhancement of delivery of AZT to CNS that have been reported are highly variable from laboratory to laboratory (7,10,20,21). Recent findings that a series of lipophilic 6-halo-ddPs exhibit activity against HIV in vitro (11,18,35,36) and that their activities were completely abrogated in the presence of an ADA inhibitor (23,35,36) coupled with preliminary indications of enhanced CNS delivery via this approach in rats (2), suggest a promising new enzyme-based strategy for improving the delivery of dideoxynucleosides to the CNS.…”
Section: Resultsmentioning
confidence: 99%
“…While a variety of targetors have been examined, derivatives of the dihydronicotinate-nicotinate redox couple have proven to be the most successful. Application of the approach to a number of drugs, including antiviral nucleosides, has been reported (1,4,7,9,10,24,25).…”
mentioning
confidence: 99%
“…As part of these efforts, we have synthesized and studied dihydropyridine derivatives (Bodor et al, 1981) of AZT and 3'-azido-2',3'-dideoxyuridine (AZdU) (Chu et al, 1990a). In vivo studies in mice indicated that the dihydropyridine derivatives significantly enhanced the delivery of the parent nucleosides to the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Chemicals 6-Chloro-2' ,3'-dideoxypurine (6-CI-ddP), 2',3'-dideoxyinosine (ddl), 6-chloro-purine base (6-CI-purine) and 3'-azido-2',3'-dideoxyuridine (AZdU) were synthesized as previously described (Chu et al, 1990a). The chemical purity of the compounds, confirmed by spectral and high-performance liquid chromatographic (HPLC) analysis, was greater than 98%.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%